2022
DOI: 10.3389/fmed.2022.821777
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of Oral and Gut Microbiomes in SARS-CoV-2 Infected Patients in Bangladesh: Elucidating the Role of Opportunistic Gut Microbes

Abstract: Coronavirus disease-2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 virus. The microbes inhabiting the oral cavity and gut might play crucial roles in maintaining a favorable gut environment, and their relationship with SARS-CoV-2 infection susceptibility and severity is yet to be fully explored. This study investigates the diversity and species richness of gut and oral microbiota of patients with COVID-19, and their possible implications toward the severity of the patient's illness and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 60 publications
4
58
1
Order By: Relevance
“…Amongst these studies, which originated from different populations in China, USA, Japan, Bangladesh, United Arab Emirates, Portugal, Germany and Hungary, the faecal microbiome of patients with COVID-19 showed decreased bacterial diversity 27 30 and reduced abundance of short-chain fatty acid (SCFA)-producing bacteria from the Lachnospiraceae, Ruminococcaceae and Eubacteriaceae families as well as increased opportunistic pathogens from Enterobacteriaceae families 27 29 , 31 37 compared with the faecal microbiome of healthy individuals. Specifically, the abundance of Faecalibacterium 27 , 28 , 31 , 33 35 , 37 , Eubacterium 28 , 34 , 37 , 38 , Coprococcus 27 , 35 , 36 , 38 , Ruminococcus 27 , 28 , 35 , Lachnospira 27 , 35 , 38 and Roseburia 27 , 35 was decreased, whereas that of Enterococcus 32 , 34 36 , Rothia 28 , 32 , 35 , 36 and Lactobacillus 27 , 35 , 36 was increased. Intriguingly, a number of studies with a modest sample size of typically ~30 patients have reported that patients with COVID-19 had a distinct gut microbiome composition compared with patients with community-acquired viral pneumonia 39 and influenza virus infection 28 , 35 .…”
Section: Covid-19 and Gut Microbiotamentioning
confidence: 99%
“…Amongst these studies, which originated from different populations in China, USA, Japan, Bangladesh, United Arab Emirates, Portugal, Germany and Hungary, the faecal microbiome of patients with COVID-19 showed decreased bacterial diversity 27 30 and reduced abundance of short-chain fatty acid (SCFA)-producing bacteria from the Lachnospiraceae, Ruminococcaceae and Eubacteriaceae families as well as increased opportunistic pathogens from Enterobacteriaceae families 27 29 , 31 37 compared with the faecal microbiome of healthy individuals. Specifically, the abundance of Faecalibacterium 27 , 28 , 31 , 33 35 , 37 , Eubacterium 28 , 34 , 37 , 38 , Coprococcus 27 , 35 , 36 , 38 , Ruminococcus 27 , 28 , 35 , Lachnospira 27 , 35 , 38 and Roseburia 27 , 35 was decreased, whereas that of Enterococcus 32 , 34 36 , Rothia 28 , 32 , 35 , 36 and Lactobacillus 27 , 35 , 36 was increased. Intriguingly, a number of studies with a modest sample size of typically ~30 patients have reported that patients with COVID-19 had a distinct gut microbiome composition compared with patients with community-acquired viral pneumonia 39 and influenza virus infection 28 , 35 .…”
Section: Covid-19 and Gut Microbiotamentioning
confidence: 99%
“…Those microbes and their genes, collectively known as the human gut microbiome, modulate host immunity 10 . To date, several studies, based on 16 S rRNA gene sequencing, have demonstrated that the human upper respiratory and gut microbiome are broadly altered in patients with COVID-19 11 16 . Although 16 S rRNA gene sequencing provides valuable insights into the general characteristics of the human microbiota, it does not offer the taxonomic resolution needed to capture sufficient sequence variation to discriminate between closely related taxa 17 .…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth analyses of our results revealed a highly significant increase in the normalized counts of Escherichia/Shigella, Megasphaera, and Prevotella. Escherichia/Shigella is a common oral and intestinal pathogen ( 22 ) also associated with changes in the human microbiome after SARS-CoV-2 infections ( 43 ). Oral Megasphaera was associated with inflammatory illnesses like rheumatoid arthritis and periodontitis ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%